Method of calculating the parameters of ultrasonic super-high-frequency transducers - Lanin V. L.; Petukhov I. B. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2013)
The paper presents a method of calculating the parameters of half-wave package ultrasonic piezoelectric emitters and step waveguides, which has an error no more than 6—8%. This method, owing to its simplicity, usability and low cost, can be effectively used for the design of ultrasonic transducers of different designs in a wide range of frequencies.